Precision Radiotherapy: 18F-FDG PET-based radiotherapy planning in Head and Neck cancers - Padma Subramanyam; Shanmuga Palaniswamy; Shah Numani (World Journal of Nuclear Medicine)
Precision medicine is gaining importance in this era of molecular imaging where the molecular features of a disease can be noninvasively assessed and treated with personalized medicine. This is especially suited for head and neck cancers (HNCa). Early stage HNCa are ideally managed with radiotherapy (RT) or surgery. Head and neck (HN) is a complex region and its tumors respond to RT differently due to dissimilar structures and moving organs such as tongue. Radiation oncologists are always in the process of trying and investigating newer RT techniques in order to achieve precise and targetted therapy to tumour/s. One such innovation is Intensity modulated RT (IMRT) using 3 Dimensional conformal RT (3DCRT). This 3DCRT resizes the radiation beams to match the shape of the tumor. Such focused dose escalation may improve local control in HNCa. Image guided RT in conjunction with IMRT is the most advanced form of RT planning being used these days. Simulation computerized tomography (CT) images are usually incorporated into RT planning module. But limitations of CT such as poor soft tissue contrast than magnetic resonance imaging and inability to clearly define solid / cystic / necrotic areas and viable tumour exist. Functional imaging such as Positron Emission Tomography (PET) has established its superiority over CT in delineating the actual site and extent of HN tumors. A combination of IMRT with BTV (Biological Tumour Volume) may be the most ideal technique to deliver a homogeneous radiation boost to tumour. This review shall discuss PET based RT planning, challenges, practical tips, and how to optimize therapy with the least side effects to the normal surrounding tissues.